Personal data protection in Ukraine via the prism of european judicial institutions’ practise - Mykola Kotenko; Ruslan Karagioz; Iryna Sopilko; Valerii Andrusiv; Hanna Yermakova (Estudios en Derecho a la Información)
The current paper intends to examine the issue of information protection, particularly personal data, based on positive international experience, aiming to revise and improve personal information protection provisions in Ukraine. Since conventional norms necessitate the use of the evolutionary interpretation approach in the context of the dynamic development of societal life, the study’s materials were international legal regulations and the European Court of Human Rights and the Court of Justice of the European Union case law. Thus, notable cases were examined in order to shed light on the developing comprehension of sensitive data and the need for enhanced security. The analysis of the court practises regarding personal data protection was conducted using a combination of general scientific and specific legal methods, namely dialectical, analytical, formal-dogmatic, comparative-legal, systemic and predictive methods. As a result of the research, key standards for personal data protection were identified, and recommendations for improving Ukrainian legislation, particularly in terms of clarity and certainty, were developed. Recognising potential implementation challenges, the article advocates for ongoing research in this field to refine and strengthen personal data protection mechanisms in Ukraine.